Internet Dalam Konteks Perpustakaan - Roni Rodhin (Pustakaloka, 2011)
The presence of internet would bring a variety of effects inall areas of human life. The impact of bias could be both a positive and negative. On the other side for libraries it would bring a disparate impact, engaged in the service and information. In the context of libraries, the internet is very helpful to disseminate informationthat is available in it. It means internet becomes a partner in the dissemination of information. Therefore, the existence of the Internet is very important for the library.